Intellectual and aesthetic approaches in Iraqi theatre texts Texts (Falah Shaker and Ali Abdul Nabi Al-Zaidi) as an example (Journal of the College of Basic Education, 2025)
Talking about the Iraqi theatrical text is often linked to talking about the life and experience of those who learned its origins and became acquainted with the art of writing and dramatizing it outside the borders of the homeland, since the Iraqi and Arab theatrical text in general is not the product of an original experience that grew and crystallized within the borders of the Arab region, but rather it is an imported experience for all countries with the exception of Greece, where it originated and its rules developed and then branched out into its other types. The theatrical text is a literary fabric that does not resemble the poetry of Al-Mutanabbi or Al-Hariri’s Maqamat in any way, although the latter may contain characters and events and perhaps also some structures that greatly resemble plotting.